Dose and duration of opioid use in patients with cancer andn non-cancer pain at an outpatient hospital setting in Malaysia: A retrospective cross sectional study - Zin, Che Suraya; Abdul Rahman, Norny Syafinaz; Ismail, Che Rokiah; Leong, Weng Choy (2016)
Aims of investigation: Prescribing of opioid analgesics have tremendously increased over the last few decades and the increase was also associated with increasing incidence of dependence, misuse and overdose related deaths. There is currently limited data available on the patterns of opioid prescribing in Malaysia. The objective of this study was to investigate the patterns of opioid prescribing and characterize the dosing and duration of opioid therapy for the treatment of cancer and non-cancer pain.